Produção de carotenoides por linhagens do gênero Rhodotorula utilizando glicerol como fonte de carbono - Castelo Branco, Leise Soares (2015)
The increased production of biodiesel has caused a sudden increase in the production of glycerol, creating an excess of this product on the market. Glycerol can be used as biotechnological processes carbon source, including the carotenoids production. The microbial carotenoids have been studied and its potential recognised over the years. The genus Rhodotorula is renowned for its ability to biossintetizar carotenoids, such as β-carotene, toruleno and torularhodin, in different proportions. This genus has been studied due to their potential for industrial production of carotenoids, once that offer advantages over other genres in terms of high growth rate and use of low cost substrates. In this context, the main objective of this work was to demonstrate the applicability of crude glycerol as a carbon source on production of carotenoids pigments for the genus Rhodotorula by submerged fermentation. The culture medium used in fermentation processes performed as follows in (g. L-1): glycerol: 20.0; yeast extract: 1.0; K2HPO4:1.0; (NH4) 2SO4:5.0 and 4.7 MgSO.H2O: 0.5. For both were prepared 100 mL of medium, inoculated with 0.1 g L-1 dry mass, and incubated at 30° C, 150 rpm for 24 hours in orbital shaker. Subsequently the fermented medium was transferred to a 2 L bottle containing 400 mL and incubated for 48 hours. The culture medium containing 500 mL was used to inoculate the fermentor, where growth continued for 240 hours under aeration rate of 1.0 vvm-1. The samples were taken at regular intervals of 24 hours for determination of biomass, glycerol, productivity, the chromaticity a* and carotenoids. After the preliminary tests of research, selected three strains of Rhodotorula genus (R. lactosa CCT 2057, R. glutinis URM 5724 e R. aurantiaca URM 5726) capable of producing biomass and synthesize carotenoids via glycerol. Testing of volumetric expansion of the fermentation medium with Rhodotorula mucilaginous CMIAT 164 and Rhodotorula aurantiaca 5726 URM compared the performance of raw glycerol and biomass production. In tests of 2 L Erlenmeyer flasks revealed the best performance of crude glycerol in the production of biomass rich in carotenoids, registering 6.2 ± 0.19 g.L-1 in Rhodotorula mucilaginous CMIAT 164 crops and biomass productivity of 0.069 ± 0.007 g.L-1.h-1 using crude glycerol as a carbon source. Inoculum test held in bioreactor, selected the times of 48 hours of fermentation (exponential phase) and 120 hours (stationary phase) for the two strains. In the fermentations conducted in 3 L bioreactors with Rhodotorula mucilaginous CMIAT 164 employing crude glycerol as carbon source, it was observed that the inoculation of the suspension from a 48 h culture propagation influenced higher biomass production values (6.35 ± 0.3 g L-1) and productivity (0.080 ± 0.004 g.L-1.h-1). The tests also revealed that the bioreactors in incubation temperature of 30 ºC and pH control in 6 were the best conditions for the synthesis of biomass and carotenoids. The cultures kept at 30 ºC registered biomass 6.5 ± 0.3 g.L-1 and 0.546 ± 0.02 mg.g-1 of carotenoids. Fermantations kept at pH 6 showed higher carotenoids production values (0.576 ± 0.02 mg.g-1). Increase in the concentration of the inoculum and the feeding strategies of bioreactor, under the conditions evaluated no impact considerably on increasing the production of biomass and carotenoid by R. mucilaginosa CMIAT 164